ANALISIS KUALITAS PELAYANAN RAWAT INAP PUSKESMAS WEDUNG II KABUPATEN DEMAK - Warsono, Hardi; Billah, Muhammad Naufal Mu’tashim (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
This research aims to find out and analyze the quality of inpatient care, and to determine the factors that affect inpatient care in Puskesmas Wedung II Demak. Puskesmas Wedung II Demak has just provided in the last two years still has some weaknesses. This research is a descriptive qualitative research. It means researcher collected the data through interviews, observation, and literature. The data information was taken from the Head of Puskesmas Wedung II, staff in charge for Inpatient care, nurse, patient and / or patient's family. In this study, researcher used the dimensions of transparency, responsiveness, assurance, empathy and direct evidence to see the quality of inpatient care in Puskesmas Wedung II. The results show that inpatient services quality of Puskesmas Wedung II Demak based on indicators that have been good that is information inpatient procedures, the responsiveness of the staff, the availability of medicines and medical equipment is quite good and adequate. Indicadotrs are not good that is does not provide transparent information related to the cost of inpatient care, complaint handling, and requirements that have to be met in accessing inpatient care, no guarantee drug information, not all staff are friendly to the patient, not separated inpatients space, and understaffed ceiling cavities in the emergency room. Awareness, regulation / service standards and infrastructure are the factors that affects the quality of inpatient care in Puskesmas Wedung II. Based on the results of this study, it can be concluded that in general inpatient care in Puskesmas Wedung II Demak pretty good, although there are some indicators that must be repaired. The researcher suggest to increase the budget to make a betterment in some parts that need to be fixed into a plan Level Health Center next year.